PERAN PEREMPUAN DALAM PENDIDIKAN BUDI PEKERTI - MUHAMMAD SHOLEH (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
Basically Islam gives the equal rights to men and womenhence there is no prohibition for a woman to develop herself either as anindividual, a mother, a wife or a society member. One of the roles she cantake is giving character education to her children. As a mother, a woman isdemanded to give affection wisely and to be a good model for her children,especially in developing children’s good personality.